Plasticity of the heat-affected zone in 9Ni steel welded pipes: evaluation of the microconstituents' deformability - Maia, Pedro Paulo Nunes (2022)
Low carbon nickel-alloyed steels have been, through decades, applied in services that demand good toughness at low temperatures. Within this group, 9Ni steel stands out as the most traditional material used to transport and store liquefied natural gas. 9Ni steels have been recently adopted in supercritical CO 2 injection systems in deepwater oil fields. The manufacture of these subsea systems involves multi-pass welding procedures, which produce a lath martensitic Heat-Affected Zone (HAZ) with high heterogeneity of microstructural features and local mechanical properties, and may introduce Local Brittle Zones (LBZ) at the Coarse-Grained HAZ (CGHAZ). A detailed microstructural investigation was conducted along the this HAZ, mapping local mechanical properties and correlating the microstructural features with the mechanical behaviour during plastic deformation. The results revealed that the highest microhardness values are found at the Super-critically reheated CGHAZ (SCR-CGHAZ), characterised by its refined microstructure and a quite low area fraction of coarse lath martensites. The Subcritically reheated CGHAZ (SC-CGHAZ) and the Intercritically reheated CGHAZ (IC-CGHAZ) – regions with wider martensite blocks and higher coarse lath area fraction – composed the softer zones of the HAZ. However, reheating at intercritical temperatures induces the formation of fresh martensite and the stabilisation C-rich retained/reversed austenite particles, which may degrade the mechanical properties at the IC-CGHAZ. Furthermore, analysis of the HAZ plasticity – focusing on the contribution of coarse martensite laths to its deformability – revealed that the CGHAZ is the only HAZ region that experiences significant strain, with the SC-CGHAZ presenting the highest strain levels. Regarding the coarse laths, Electron Backscatter Diffraction (EBSD) analyses on progressively deformed specimens showed that these constituents might carry plasticity during most of the early plastic regime until the microstructure reaches a state of high constraint, participating in a hierarchic plastic deformation, which is initiated with the strain-induced martensitic transformation of interlath austenite films. The present thesis brings solid results regarding the microstructural characterisation of the HAZ in 9Ni steel girth welded pipes, aiding in understanding how multipass welding processing may impact the mechanical properties of the HAZ. It also brings new insights on the mechanical behaviour of lath martensite, assessing how its microconstituents, especially the coarse martensite laths, may contribute to its deformability.